A Community Based Program Promotes Sanitation - María Laura Alzúa; Habiba Djebbari; Amy J. Pickering (Institute of Labor Economics (IZA), 2018)
Basic sanitation facilities are still lacking in large parts of the developing world, engendering serious environmental health risks. Interventions commonly deliver in-kind or cash subsidies to promote private toilet ownership. In this paper, we assess an intervention that provides information and behavioral incentives to encourage villagers in rural Mali to build and use basic latrines. Using an experimental research design and carefully measured indicators of use, we find a sizeable impact from this intervention: latrine ownership and use almost doubled in intervention villages, and open defecation was reduced by half. Our results partially attribute these effects to increased knowledge about cheap and locally available sanitation solutions. They are also associated with shifts in the social norm governing sanitation. Taken together, our findings, unlike previous evidence from other contexts, suggest that a progressive approach that starts with ending open defecation and targets whole communities at a time can help meet the new Sustainable Development Goal of ending open defecation.
Keywords: Q53; Q58; D78; 330; sanitation; behavioral change; community-based intervention; social norm